Tecnologías para la remoción de colorantes y pigmentos presentes en aguas residuales. Una revisión (2015)
Dyes and pigments are beginning to do in the country considered as a series of compounds that can have toxicological characteristics beyond the aesthetic aspects in wastewater. This review attempted to cluster the most effective treatments for the removal, destruction and mineralization of dyes and pigments present in wastewater depend on the physicochemical properties of the constituent molecules. The kinetics of removal of BOD, COD, "real" colour and "apparent" in effluents, in addition to operating times were studied to determine the set of physical technologies, chemical, biological and combined major and influence nowadays. Among the most relevant treatment technologies highlights the adsorption and filtration, advanced oxidation technologies (photocatalysis, ozonation, fenton / UV, electrocoagulation, etc.) and sequential biological processes (type anaerobic - aerobic). The influence of variables such as the pH, the initial concentration of dye and solubility, among others, on the kinetics of removal of specific dyes are evident.